Tłumacz zdemaskowany. Wybrane teksty Dubravki Ugrešić w przekładzie Doroty Jovanki Ćirlić — spojrzenie krytyczne - Jawoszek, Agata (Przekłady Literatur Słowiańskich, 2015)
Unmasked translator Dubravka Ugrešić`s selected texts translated by Dorota Jovanka Ćirlić — a critical view On the selected Dubravka Ugrešić’s texts translated into polish by Dorota Jovanka Ćirlić, on the one hand the most popular on the second hand the most criticized by the local Slavists, contemporary Polish translator of Balkan literature, we can analyze the question of a presence (or absence) of translators in the text. On the example of translation of the novel Stefica Cvek in the Jaws of Life and book of essay There is no one at home, we analyze the strategies of translation and individual translator’s solutions as well as their importance in the context of “freedom of translator” and its impact on the process of building author’s position and reception of texts in different cultural and linguistic context. Key words: Dubravka Ugrešić, Dorota Jovanka Ćirlić, translator’s competence, domestification, strategy of translation, literality, semantic change, translation of idioms